1997
DOI: 10.1021/ja964352a
|View full text |Cite
|
Sign up to set email alerts
|

A Multiplet Analysis of Fe K-Edge 1s → 3d Pre-Edge Features of Iron Complexes

Abstract: X-ray absorption Fe-K edge data on ferrous and ferric model complexes have been studied to establish a detailed understanding of the 1s f 3d pre-edge feature and its sensitivity to the electronic structure of the iron site. The energy position and splitting, and intensity distribution, of the pre-edge feature were found to vary systematically with spin state, oxidation state, geometry, and bridging ligation (for binuclear complexes). A methodology for interpreting the energy splitting and intensity distributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

164
1,562
3
3

Year Published

2001
2001
2010
2010

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 1,280 publications
(1,751 citation statements)
references
References 86 publications
(82 reference statements)
164
1,562
3
3
Order By: Relevance
“…The two spectra are very similar, including the pre-edge feature at ca. 7113 eV, which corresponds to the forbidden transition 1s-3d [5,15,16]. The intensity of the transition is consistent with the proposed octahedral geometry of the Fe centre in these metalloproteins.…”
Section: Xanes Regionsupporting
confidence: 83%
“…The two spectra are very similar, including the pre-edge feature at ca. 7113 eV, which corresponds to the forbidden transition 1s-3d [5,15,16]. The intensity of the transition is consistent with the proposed octahedral geometry of the Fe centre in these metalloproteins.…”
Section: Xanes Regionsupporting
confidence: 83%
“…Previous studies on molecular systems have shown reasonable empirical correlations between experimental d-d transitions and ground state d-orbital energy differences, [84][85][86] which also correlated to TD-DFT calculation results. 86 Core-hole effects on ligand field splittings using a cobalt atom with a nuclear charge of Fe have been evaluated elsewhere; 87,88 trends in ligand field effects between compounds were found to be largely unaffected by the presence of the core hole. Mulliken population analysis was performed as implemented in ADF.…”
Section: Dft Calculationsmentioning
confidence: 99%
“…21 The preedge spectrum of 9-P consists of two peaks centered at 7111.8 and 7113.5 eV (Figure 3, inset; Table 1). This preedge energy range is characteristic of ferrous complexes, and the total preedge area of 12.3 units and the area distribution between the two peaks indicate high-spin five-coordinate iron centers in 9-P. 21 The preedge fit for 11 reveals two peaks of comparable intensity at 7113.0 and 7114.5 eV with the total area of 7.1 units (Table 1). This energy range and area distribution are typical for high-spin ferric complexes with distorted-octahedral geometry.…”
Section: X-ray Absorption Spectroscopy (Xas)mentioning
confidence: 99%